Distribution of arsenic compounds in Plantaginaceae and Cyperaceae plants growing in contaminated soil. Issue 10 (25th November 2016) - Tremlová, Jana; Száková, Jiřina; Golka, Vladan; Babková, Radka; Najmanová, Jana; Tlustoš, Pavel
ABSTRACT: The ability of plant species to accumulate arsenic (As) species in the biomass from As-contaminated soils is variable. Among the plants widely grown at the As-contaminated locations, Plantaginaceae and Cyperaceae families belong to the frequent ones. In this study, the ability of Plantago lanceolata ( Plantaginaceae ) and three wetland plant species representing the family Cyperaceae ( Carex praecox, Carex vesicaria, and Scirpus sylvaticus ) naturally occurring in the soils with an elevated As in the Czech Republic were investigated. The plants were cultivated under controlled conditions in an As-contaminated soil reaching 735 mg kg −1 of the total As. The total As in plants reached up to 8.3 mg kg −1 in leaves, and up to 155 mg kg −1 in roots of C. praecox. Dominant As compounds were arsenite and arsenate with a small abundance of dimethylarsinic acid (DMA) in all the plant species. In Cyperaceae, small percentages of arsenobetaine (AB) and arsenocholine (AC) were detected, suggesting the ability of these plants to transform As into less toxic compounds. Moreover, the important role of As(V) sequestration on iron plaque on the root surface of Cyperaceae was confirmed. In this context, root washing with oxalic acid partially disrupted the iron plaque for the better release of arsenate.